The effects of managerial gender and education on firm performance - Nguyen, Liem; Vo, Diem; Pham, Hien; Nguyen, Van; Than, Yen; Le, Ha (Journal of International Economics and Management, 2024)
The role of women has been increasingly affirmed as gender equality has become the norm, particularly when it comes to how firms should be managed. In addition, education instills knowledge that could change managerial perspectives, thus affecting the ways they manage firms. This study uses a dataset covering 617 non-financial firms listed on the Vietnamese stock market from 2010 to 2021 to examine the impact of managerial gender and education on firm performance, measured in accounting- and market-based values. The System Generalized Method of Moments was employed to address endogeneity and other defects normally associated with panel data. The results reveal that having female chief executive officers (CEOs) positively affects firms. Additionally, a CEO’s educational background positively affects both accounting- and market-based measures. The study provides new evidence of the positive effects of female CEOs and highly educated CEOs on firm performance compared with some extant studies in Vietnam. Based on the research findings, relevant suggestions are proposed regarding the welcoming features of CEOs in managing firms in Vietnam.